Design, synthesis and luminescence properties of Ba2YB2O6Cl‐ and Ba2YB2O6F‐based phosphors. (22nd June 2014) - Chen, Wanping; Yang, Xin; Liu, Yan; Dai, Xiaoyan
Abstract Using a high‐temperature solid‐state reaction, the chlorine in Ba2YB2O6Cl is gradually replaced by F, and a new compound with the nominal chemical formula Ba2YB2O6F and two phosphors doped with Ce3+ and Eu3+, respectively, are obtained. X‐Ray diffraction and photoluminescence spectroscopy are used to characterize the as‐synthesized samples. The as‐synthesized Ba2YB2O6Cl exhibits bright blue emission in the spectral range ~ 330–410 nm with a maximum around 363 nm under X‐ray or UV excitation. Ba2YB2O6F:0.01Ce3+ exhibits blue emission in the range ~ 340–570 nm with a maximum around 383 nm. Ba2YB2O6F:0.01Eu3+ exhibits a predominantly 5D0–7 F2 emission (~610 nm) and the relative intensities of the 5D0–7 F0, 1, 2 emissions are tunable under different wavelength UV excitation. The luminescence behaviors of the two phosphors are explained simply in terms of the host composition and site occupancy probability of Ce3+ and Eu3+, respectively. The results indicate that these phosphors have potential application as a blue phosphor or as a red phosphor. Copyright © 2014 John Wiley & Sons, Ltd.